The Effect Of Teacher Recruitment, Commitment And Compensation On Teacher Performance In SD Negeri 390 And SD Negeri 395 Kecematan Muara Batang Gadis Mandailing Natal Regency - Bolo Ansah Nasution; Yohny Anwar; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2024)
Human Resources (HR) is the most important asset in the implementation of education in schools. In the era of globalization, schools are required to have quality human resources so that they are able to improve the quality of education. As stated in Law of the Republic of Indonesia No. 20 of 2003 concerning the National Education System Article 3 which reads, "National education functions to develop abilities and shape the character and civilization of a dignified nation in order to educate the life of the nation, aiming to develop the potential of students to become human beings who believe in and fear God Almighty, have noble character, healthy, knowledgeable, capable, creative, independent and become democratic and responsible citizens". This study was conducted to determine the Influence of Teacher Recruitment, Commitment and Compensation on Teacher Performance This research was conducted in SD Negeri 390 and SD Negeri 395 Kecematan Muara Batang Gadis Mandailing Natal Regency, the population of this study is 35 teachers and the sample used is a saturated sample because counting all populations into samples this type of research is quantitative data collection which is used by spreading the research model used is a multiple linear regression with the SPSS version 25 measuring tool, the results of this study are as follows: Recruitment has a negative and significant effect on Teacher Performance with a value of -0.445 and sig 0.025, Commitment has a positive and significant effect on Teacher Performance with a value of 0.845 and sig 0.000, Compensation has a non-significant positive effect on Teacher Performance with a value of 0.258 with sig 0.136.